Smart power security system - Haque, Md. Enzamul; Jony, Imrul Azam; Ali, Mir Shadman; Islam, Md. Toriqul (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.